Implementasi Room Database pada Aplikasi SFA untuk PT. X berbasis Android - Jerry Tandiari; Yulia Yulia; Anita Nathania Purbowo (Jurnal Infra, 2019)
PT. X is a company engaged in the distributor of building materials. Application owned by PT. X is currently unable to accommodate employees' needs to record sales when there is no internet connection and cannot record the location of sales employees when making sales order transactions. Therefore, a new application is needed that can store temporary data on the user's device when there is no internet connection.In this journal an Android application will be created that can help sales employees at PT. X conducts sales transactions and saves data offline on the device. Applications that are made will also be supported by the GPS feature to record the location of employees when making sales orders.The final result of this journal is an Android-based sales application that can help sales employees from PT. X to see the data needed and make transactions through applications that are made either when there is an internet connection or not.